EVALUATION OF STABILITY OF ROPINIROLE HYDROCHLORIDE AND PRAMIPEXOLE DIHYDROCHLORIDE MICROSPHERES AT ACCELERATED CONDITION - Kar, Koyel; Pal, R. N.; Nandi, Gouranga (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of the present work was to conduct accelerated stability study as per international council for harmonisation (ICH) guidelines and to establish shelf life of controlled release dosage form of ropinirole hydrochloride and pramipexole dihydrochloride microspheres for a period of 6 mo. Methods: Most optimized batch of ropinirole hydrochloride and pramipexole dihydrochloride (F12 and M12 respectively) were selected and subjected to exhaustive stability testing by keeping the sample in stability oven for a period of 3 and 6 mo. Various parameters like surface morphology, particle size, drug content, in vitro drug release and shelf life were evaluated at 3 and 6 mo period. The surface morphology of the formulated microspheres was determined by scanning electron microscopy (SEM). The particle size of the microspheres was estimated by optical microscopy method. The drug content was assayed by the help of ultra-violet spectrophotometer (UV). The in vitro drug release was performed by using Paddle II type dissolution apparatus and the filtrate was analyzed by UV spectrophotometer. The shelf life of the optimized microspheres was calculated by using the rate constant value of the zero-order reaction. Results: A minor change was recorded in average particle size of F12 and M12 microspheres after storage for 6 mo. For F12 and M12, initially the particle size was 130.00 µm and 128.92 µm respectively and after 6 mo it was found to be 130.92 µm and 128.99 µm respectively. There was no change in surface morphology of F12 and M12 microspheres after 6 mo of storage. The shape of microspheres remained spherical and smooth after 6 mo. An insignificant difference of drug content was recorded after 6 mo compared to the freshly prepared formulation. For F12 and M12, 94.50% and 93.77% of the drug was present initially and after 6 mo 94.45% and 93.72% of the drug was recorded. In vitro drug release was recorded after 6 mo for F12 and M12. Initially, 97.99% and 97.69% of the drug was released till 14th hour respectively for F12 and M12. After 6 mo, 98.23% and 97.99% of the drug was released respectively. The percentage residual drug content revealed that the degradation of microspheres was low. Considering the initial percentage residual drug content as 100%, 99.94% of the drug was recorded for both F12 and M12. The shelf life for F12 and M12 was found to be 10 y 52 d and 10 y 70 d respectively which were determined by the zero-order kinetic equation. Conclusion: A more or less similar surface morphology, particle size, drug content and percent of drug release before and after stability study confirmed the stability of F12 and M12 microspheres after storage for 6 mo and prove the efficacy of the microspheres in the site-specific delivery of drugs in Parkinson's disease.